'In the hospital there are no care guidelines': experiences and practices in perinatal loss in Spain. Issue 4 (10th January 2020) - Fernández‐Alcántara, Manuel; Schul‐Martin, Laetitia; García Caro, Mª Paz; Montoya‐Juárez, Rafael; Pérez‐Marfil, Mª Nieves; Zech, Emmanuelle
Abstract : Background and objectives: Healthcare professionals play an important role in supporting and attending to families that experience a perinatal loss. Previous research has identified the existence of obstacles that professionals may encounter during their practices. The main objective of the current research was to identify and examine the subjective experiences and practices of experienced professionals attending to perinatal loss in the hospital context in Spain. Design: Qualitative descriptive design. Setting: Three different hospitals in Spain. Participants: Sixteen professionals were interviewed, including doctors, nurses, midwives, nursing assistants, a psychologist and a funeral home manager. Methods: Individual semi‐structured interviews focusing on three areas were carried out: practices with the baby–foetus, practices with parents and interaction with the team. A thematic analysis was performed using the three main focuses of the semi‐structured interview (deductive approach) and the codes that emerged from the data (inductive approach). Results: Regarding guideline‐based care for the baby/foetus, participants made a distinction between the initial process of care for the baby and the decision‐making process with parents. Where support for families was concerned, participants identified considerable variability in the practices used and lack of organisational and care guidelines, psychological support and follow‐up. Finally, interactions with other team members were perceived as a source of support, although participants identified a significant lack of coordination. Conclusion: Participants reported variability of practices in care for the baby and parents, lack of continuity‐of‐care guidelines and the importance of support from a coordinated healthcare team.